Dependence of the Equivalent Circulation Density of Formate Drilling Fluids on the Molecular Mass of the Polymer Reagent - Ekaterina Leusheva (MDPI AG, 2021)
Construction of offshore gas wells is characterized by increased requirements for both the technological process in general and the technological parameters of drilling fluids in particular. Parameters and properties of the used drilling muds must meet a large number of requirements. The main one is the preservation of the permeability of the reservoirs, in addition to the environmental and technological concerns. At the same time, pressures in the productive formation at offshore fields are often high; the anomaly coefficient is 1.2 and higher. The use of barite in such conditions can lead to contamination of the formation and a decrease in future well flow rates. In this regard, the development and study of the compositions for weighted drilling muds is necessary and relevant. The paper presents investigations on the development of such a composition based on salts of formic acid (formates) and evaluates the effect of the molecular weight of the polymer reagent (partially hydrolyzed polyacrylamide) on the equivalent circulation density of the drilling fluid. The result of the work is a formate-based high-density drilling mud with no barite added. Application of such a mud will preserve the permeability of the productive formation.